Assessment of the perceived impact of diabetes on quality of life in a group of South African diabetic patients - Katzenellenbogen, Leanne (Stellenbosch : Stellenbosch University, 2008)
Thesis (MNutr (Interdisciplinary Health Sciences. Human Nutrition))--Stellenbosch University, 2008.